Random and AB diblock copolymers of tricyclodecanemethanol urethane methacrylate with styrene: synthesis and morphology characterization - Deepak, V. D.; Asha, S. K. (Journal of Polymer Science Part A: Polymer Chemistry, 2008)
A monomer design having a bulky terminal tricyclodecane (TCD) unit linked via hydrogen bondable urethane to an ethyleneoxy methacrylate unit, and capable of generating three-dimensional honeycomb patterns upon solvent casting has been investigated. Random copolymers as well as a diblock copolymer Poly(Sty42-b-TCD18) of this monomer with styrene were prepared by free-radical polymerization route and atom transfer radical polymerization (ATRP) route. Morphology characterization was carried out using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. Particle size was measured by dynamic light scattering measurements (DLS). Irrespective of the wide differences in molecular weight and polydispersity index values, the random copolymers having TCD content >30 mol % were found to form microporous films upon solvent casting from a THF/water 9:1 solvent combination. The amount of TCD in the copolymer was found to have an influence on the pore size formed. The diblock copolymer formed microspheres ∼200 nm in diameter. The thermal properties of all the polymers were studied using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), and the copolymers were found to have good thermal stability. © 2008 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 46: 1278–1288, 2008